EFEKTIFITAS BERKUMUR LARUTAN EKSTRAK BENGKUANG (PACHYRHIZUS EROSUS) TERHADAP PLAK INDEKS SISWA KELAS IV DAN V SDN 15 AMPANG GADANG KECAMATAN AMPEK ANGKEK KABUPATEN AGAM TAHUN 2019 - M. Faisal; Zulfikri Zulfikri (Ensiklopedia of Journal, 2020)
The most common dental and oral disease is caries and periodontal disease. The main cause of both diseases is plaque, plaque is a soft deposit consisting of a collection of bacteria that multiply in a matrix. The formation of dental plaque can be prevented by gargling yam extract (Pachyrhizus erosus) with a concentration of 5%, 10% and 15%. The purpose of this study was to determine the effect of giving yam extract solution to the index of dental plaque. This research was conducted to determine the effectiveness of gargling yam extract solution (pachyrhizus erosus) on plaque index grade IV and V SDN 15 students at Ampang Gadang Ampek Angkek Subdistrict, Agam Regency in 2019. The scope of this study discusses the differences in gargling using yam extract (pachyrhizus erosus ), index plaque. There was a significant difference in the plaque index of gargling of yam extract (pachyrhizus erosus) solution in grade IV and V sdn 15 students of Ampang Gadang, Ampek Angkek District, Agam Regency. Utilization of fruits that are easily obtained locally to improve the dental health status of school-age children. The design of this study uses a quasi- experimental method ("quasi experiment") with a "pretest" and "posttest" design. The "pretest" and "posttest" designs carried out have an observation and treatment pattern. With a population of 72 people. Samples were taken by "purposive sampling" technique, the way the data was collected was by checking the plaque index, the data were analyzed by non-parametric statistical tests, the research results were significant differences between the plaque index scores before (pre-test) and after (post-test) gargling of yam extract solution (pachyrhizus erosus) both with a concentration of 5% .10% or 15% solution, with the highest average reduction in plaque index at a concentration of 10% solution.